2019
DOI: 10.2106/jbjs.18.00853
|View full text |Cite
|
Sign up to set email alerts
|

Malpractice Litigation Following Traumatic Fracture

Abstract: Background: Poor clinical outcomes and adverse events following orthopaedic trauma are common, which may lead to litigation. To our knowledge, factors associated with litigation following fracture care have not previously been evaluated. Methods: A retrospective review of fracture-related malpractice lawsuits from 1988 to 2015 was completed utilizing VerdictSearch (ALM Media Properties), a medicolegal database. Defendant and plaintiff characteristics al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 12 publications
1
25
0
1
Order By: Relevance
“…Our results were similar to those of many other studies. A retrospective review of fracture-related malpractice lawsuits from 1988 to 2015 in America showed that the mean age of the plaintiff was 48.5±15.2 years and the most commonly involved anatomical sites were the spine and femur [ 9 ]. Klimo et al [ 10 ] reported that the lumbar spine was the most common anatomic area involved in orthopedic medical malpractice cases.…”
Section: Discussionmentioning
confidence: 99%
“…Our results were similar to those of many other studies. A retrospective review of fracture-related malpractice lawsuits from 1988 to 2015 in America showed that the mean age of the plaintiff was 48.5±15.2 years and the most commonly involved anatomical sites were the spine and femur [ 9 ]. Klimo et al [ 10 ] reported that the lumbar spine was the most common anatomic area involved in orthopedic medical malpractice cases.…”
Section: Discussionmentioning
confidence: 99%
“…It is difficult to quantify the rate at which healthcare systems are justified in accepting the failure to detect findings. Certainly, false negatives are likely to represent the most deleterious of these errors; borne-out by the evidence on litigation for missed fractures both in the UK [ 6 , 22 ] and abroad [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…They found that males and elderly patients were significantly less likely to file a claim, whereas increased comorbidity was positively associated with a claim [ 21 ]. However, a majority of male plaintiffs has also been described in a study looking at litigation after traumatic fractures [ 22 ]. Although we had no information about comorbidities, the claims in our cohort were mostly filed by young, female patients.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the limitations, we feel that this study provides valuable information for the orthopedic/ trauma surgical community. Although claims have been previously studied in orthopedic fracture surgery, this study represents the largest cohort that focuses on foot/ankle surgery [ 22 , 35 ]. Given the high complication rate in this area of orthopedic surgery, it is important to identify pitfalls in (operative) care and communication, not only to prevent malpractice claims, but to improve the quality of care.…”
Section: Discussionmentioning
confidence: 99%